Case Study Analysis of Success MDGs per capita Indonesian National Income toward CO2 Emissions Using Environmental Kuznets Curve - Dwiyanto, D (Universitas Muhammadiyah Surakarta, 2018)
The Indonesian government has mainstreamed the MDGs in the National Long Term Development plan (RPJPN 2005-2025), National Medium Term Development Plan (RPJMN 2004-2009 and 2010-2014), the Program Annual Work Plan (RKP) and document the State Budget (APBN ) more specifically on the 7 th goal is to preserve the environment. This study aimed to determine the effect of economic growth on emissions of CO2in Indonesia. This analysis uses Kuznets curve describes the relationship between economic growth as measured by per capita income to the level of environmental degradation and will result in a curve with an inverted U shape (Inverted U Curve) with the type of data used is secondary data in the form of time series data of national income and emissions of CO2 in Indonesia in 1960 until 2010 it was assumed that vulnerable between the time constant. The variables in the study are divided into two independent variables national income per capita of Indonesia and the dependent variable CO2 gas emissions, Based on these results CO2 emission levels the forest area in Indonesia in the descriptive analysis of consecutive increase and the damage / deficiency in the period 1960-2010. This study shows that the Enviroment Kuznets Curve (EKC) is not applicable in Indonesia in the case of CO2 emissionswith national income per capita, shown in the regression line which tends to rise. The researchers concluded that Indonesia is still in the phase 1 where the higher national income per capita higher the emissions of CO2.